2022
DOI: 10.1186/s12879-022-07385-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing and vaccination to reduce the impact of COVID-19 in nursing homes: an agent-based approach

Abstract: Background Efforts to protect residents in nursing homes involve non-pharmaceutical interventions, testing, and vaccine. We sought to quantify the effect of testing and vaccine strategies on the attack rate, length of the epidemic, and hospitalization. Methods We developed an agent-based model to simulate the dynamics of SARS-CoV-2 transmission among resident and staff agents in a nursing home. Interactions between 172 residents and 170 staff based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Heterogeneous vaccine was indicated for high-income countries in two (0.5%) articles [ 106 , 382 ]. In 95 articles (23.1%), the difference in days between administered doses were considered; out of these, 22 articles (23.2%) considered a 21-day interval between doses [ 55 , 60 , 69 , 100 , 122 , 133 , 134 , 140 , 187 , 216 , 217 , 221 , 302 , 303 , 329 , 330 , 335 , 342 , 383 , 384 , 424 , 425 ], while 22 (23.2%) considered a period of 21- to 28-day interval [ 42 , 90 , 116 , 119 – 121 , 136 , 142 , 151 , 155 , 184 , 204 , 205 , 258 , 260 , 273 , 324 , 328 , 351 , 354 , 356 , 366 ]. Additionally, 11 (11.6%) articles considered a period equal to or greater than three months [ 203 , 211 , 222 , 269 , 300 , 314 , 317 , 333 , 334 , 350 , 361 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous vaccine was indicated for high-income countries in two (0.5%) articles [ 106 , 382 ]. In 95 articles (23.1%), the difference in days between administered doses were considered; out of these, 22 articles (23.2%) considered a 21-day interval between doses [ 55 , 60 , 69 , 100 , 122 , 133 , 134 , 140 , 187 , 216 , 217 , 221 , 302 , 303 , 329 , 330 , 335 , 342 , 383 , 384 , 424 , 425 ], while 22 (23.2%) considered a period of 21- to 28-day interval [ 42 , 90 , 116 , 119 – 121 , 136 , 142 , 151 , 155 , 184 , 204 , 205 , 258 , 260 , 273 , 324 , 328 , 351 , 354 , 356 , 366 ]. Additionally, 11 (11.6%) articles considered a period equal to or greater than three months [ 203 , 211 , 222 , 269 , 300 , 314 , 317 , 333 , 334 , 350 , 361 ].…”
Section: Resultsmentioning
confidence: 99%
“…All models exploring vaccination found that it could help reduce COVID-19 morbidity and mortality, especially in LTCFs [23,28,31,33,52,[63][64][65][66][67]. However, some studies also noted that vaccination benefits could be hindered by high levels of community SARS-CoV-2 circulation [31,65] or by reduced adherence to contact precautions within facilities concomitant with vaccine rollout, for instance due to pandemic fatigue or risk compensation [52].…”
Section: Evaluating Vaccination Strategiesmentioning
confidence: 99%
“…The most universal finding is that more frequent testing leads to greater reductions in nosocomial transmission [12,14,21,23,24,[30][31][32][33][34][35][36][37][38][39][40]. Similarly, increasing daily testing capacity has been found to limit nosocomial transmission [27,41].…”
Section: Evaluating and Optimizing Surveillance Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, these efforts are hindered by the limitations of compartmental models and hence they are not able to incorporate subject‐specific risk and contact information. Given this, another stream of work, which has recently gained momentum, focuses on constructing more accurate agent‐based simulations that overcome these drawbacks (e.g., Faucher et al, 2022; Gomez Vazquez et al, 2022; Lee, Zabinsky, et al, 2022; Trad & El Falou, 2022). Although this line of work can provide valuable insights on the impact of certain policies on the disease dynamics, they unfortunately do not investigate the structure and composition of optimal vaccine distribution strategies.…”
Section: Introduction Motivation and Backgroundmentioning
confidence: 99%